El descubrimiento de hidrocarburos aromáticos policíclicos nitrados de estructura inesperada - Squadrito, Giuseppe (1989)
The reaction mechanism of polyciclic aromatic hydrocarbonsand nitrogen dioxide in solvents of low polarity in vol ves free radicals. The re-action products obtained under these conditions are similar to those found inambient air sarnples, suggesting a common reaction mechanism.